1985
DOI: 10.1210/endo-117-5-2085
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamo-Pituitary Regulation of Cytochrome P-45015βApoprotein Levels in Rat Liver*

Abstract: The regulation of the sexually differentiated steroid sulfate 15 beta-hydroxylase, cytochrome P-450(15) beta of female rat liver has been investigated. Specific antibodies raised to isozyme P-450(15) beta were used with the Western blot technique to quantitate the specific levels of P-450(15) beta in liver microsomes. The method demonstrated that the levels of the protein are about 16-fold higher in female than in male microsomes and also showed that the specific microsomal content of P-450(15) beta is control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 28 publications
4
38
0
2
Order By: Relevance
“…Sex hormones, via their effects on the pattern of pituitary growth hormone secretion, 12 play a major role in the regulation of this gene. 10,11,33 Thus, in this and other work, 11 estradiol administration to male rats induced expression of CYP2C12, and the combination of ovariectomy with testosterone administration abolished expression of CYP2C12 in female rats. 11,37 Using intact and hypophysectomized rats, it has been demonstrated that estradiol exerts its regulatory effect on CYP2C12 by stimulating the female continuous pattern of growth hormone release.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Sex hormones, via their effects on the pattern of pituitary growth hormone secretion, 12 play a major role in the regulation of this gene. 10,11,33 Thus, in this and other work, 11 estradiol administration to male rats induced expression of CYP2C12, and the combination of ovariectomy with testosterone administration abolished expression of CYP2C12 in female rats. 11,37 Using intact and hypophysectomized rats, it has been demonstrated that estradiol exerts its regulatory effect on CYP2C12 by stimulating the female continuous pattern of growth hormone release.…”
Section: Discussionsupporting
confidence: 71%
“…10,11,33 Thus, in this and other work, 11 estradiol administration to male rats induced expression of CYP2C12, and the combination of ovariectomy with testosterone administration abolished expression of CYP2C12 in female rats. 11,37 Using intact and hypophysectomized rats, it has been demonstrated that estradiol exerts its regulatory effect on CYP2C12 by stimulating the female continuous pattern of growth hormone release. 11,12 In the present study, serum estradiol concentrations were increased (and testosterone was decreased) in BDL female rats, and similar hormonal changes occur in male rats after BDL.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations